Photometric monitoring of WZ Sge - Boffin, H.; Harlaftis, E.; Papadimitriou, C.; Gazeas, K.; Brinias, A. (5th Hellenic Astronomical Conference, 2001)
The cataclysmic variable, WZ Sge, and one of prototype of of the SU Uma-type dwarf nova sub-class, went into outburst on July 23 of this year. This is its first outburst since 23 years. The brightness and rarety of the event has perhaps made it the most observed object of the year. From July 29 on, we have started a photometric monitoring of this system, mainly with B-band time series with the 1.2m telescope at Kryoneri Korinthias (Greece). Here, we will present the first preliminary light curves obtained, covering the first two and a half weeks of the outburst, from July 29 to August 9, when the star was in steady decline up to when it started to show superhumps. Our on-going monitoring will continue until December 2001.